(untitled) (Simbiótica. Revista Eletrônica, 2020)
The objective of this article is to present some of the basic components of the scenario where the war of the curves takes place and that allow us to approach the Pandemic as an epistemic phenomenon that implies a restructuring of a planetary sensibilities policy. To achieve this objective, we have followed the following strategy: a) the connection between Truth, Curves and Facts is briefly exposed; b) the understanding of the origin of the Pandemic is made explicit; c) the “warlike metaphor” used in the “combat” Against the Pandemic; d) proposes a look at the situation of planetarization; e) inquires about the state of “European reason”; f) analyzes the effects of social distance; g) presents the preponderance of the social networks in everyday life; h) reflecting on the “sense of emergency” of the Pandemic; and i) some postcards are opened to continue thinking. The article ends by advocating to continue investigating the hundreds of thousands of interstitial practices that permeate in a pandemic as traces that allow us to see the exit routes for a cornered humanity. Keywords: Pandemic; war; statistics; sensibilities.